The effect of green tea on prostate specific antigen (PSA): A systematic review and meta-analysis of randomized controlled trials - Elham Sharifi-Zahabi; Fatemeh Hajizadeh-Sharafabad; Hadi Abdollahzad; Afsaneh Dehnad; Farzad Shidfar (Elsevier, 2021)
Background: Prostate cancer is a major malignancy, affecting men, worldwide. The protective effect of green tea consumption on prostate cancer has been reported in several studies; however, the findings are equivocal. Objective: The aim of this study was to evaluate the effects of green tea on PSA level, by conducting a systematic review and meta-analysis of randomized controlled trials. Methods: We searched online databases, including PubMed, Scopus, and Web of Science, up to 11 Aug 2020, to obtain relevant publications. The publication search was not limited by language or date. Results: A total of 2488 records were identified in the systematic search; from these, seven were included in the meta-analysis. The overall analysis showed no significant changes in PSA levels in subjects treated with green tea, (WMD: ‒0.60 ng/mL; 95 % CI: ‒1.32, 0.12 ng/mL; P = 0.104, I2 = 93.80 %, P heterogeneity<0.001). Subgroup analysis based on geographical location showed that green tea significantly reduced PSA level in the USA population (WMD: ‒1.02 pg/mL, 95 % CI: ‒1.30, ‒0.73, P < 0.001) compared to non-USA populations (WMD: ‒0.22 pg/mL, 95 % CI: ‒0.95, 0.50, P = 0.539) (P < 0.001). Conclusion: The results of this review show that green tea has no significant effect on PSA level. However, due to the heterogeneity among studies more consistent clinical trials, with larger sample sizes are required.